Vertical nanowire probes for intracellular signaling of living cells - Lee, Ki-Young; Kim, Ilsoo; Kim, So-Eun; Jeong, Du-Won; Kim, Ju-Jin; Rhim, Hyewhon; Ahn, Jae-Pyeong; Park, Seung-Han; Choi, Heon-Jin (SPRINGEROPEN, 2014)
The single living cell action potential was measured in an intracellular mode by using a vertical nanoelectrode. For intracellular interfacing, Si nanowires were vertically grown in a controlled manner, and optimum conditions, such as diameter, length, and nanowire density, were determined by culturing cells on the nanowires. Vertical nanowire probes were then fabricated with a complimentary metal-oxide-semiconductor (CMOS) process including sequential deposition of the passivation and electrode layers on the nanowires, and a subsequent partial etching process. The fabricated nanowire probes had an approximately 60-nm diameter and were intracellular. These probes interfaced with a GH(3) cell and measured the spontaneous action potential. It successfully measured the action potential, which rapidly reached a steady state with average peak amplitude of approximately 10 mV, duration of approximately 140 ms, and period of 0.9 Hz.
Keywords: FIELD-EFFECT TRANSISTORS; CONTROLLED GROWTH; SILICON CHIP; NERVE-CELLS; NEURONS; ARRAYS; DEVICE; NETWORKS